Mathematics of Finance - Hummel, Paul Matthew; Seebeck, Charles Louis (New York: McGraw-Hill, 1971)
Just like past editions, this edition also entails the treatment of simple interest and simple discount; develops gradually and logically through the topics of compound interest, annuities with their many applications perpetuities, bonds, and depreciation; and ends with an elementary treatment of the fundamentals of life insurance.
ne 26/02/2018
Loan
Keywords: Business Mathematics